Contribution of drone photogrammetry to 3D outcrop modeling of facies, porosity, and permeability heterogeneities in carbonate reservoirs (Paris Basin, Middle Jurassic). (January 2021) - Thomas, Hadrien; Brigaud, Benjamin; Blaise, Thomas; Saint-Bezar, Bertrand; Zordan, Elodie; Zeyen, Hermann; Andrieu, Simon; Vincent, Benoît; Chirol, Hugo; Portier, Eric; Mouche, Emmanuel
Abstract: This study showcases the value of drone photogrammetry in creating a meter-scale geological model of complex carbonate geobodies. Although drone photogrammetry is now commonly used for modeling the sedimentary facies and architecture of sandstone outcrops, its use is not widespread in creating geomodels of carbonate geobodies. Drone photogrammetry can generate accurate line-drawing correlation and detailed architecture analysis along inaccessible vertical faces of outcrops and permits observations of unreachable places. This work models the Bathonian limestones of Massangis quarry (Burgundy) as an example. The quarry covers an area of 0.4 km 2 and is considered as an analogue for the Oolithe Blanche geothermal reservoir in the center of the Paris Basin. The Massangis quarry model represents a good analogue for reservoir microporosity and secondary porosity associated with dedolomitization. Ten facies are described and grouped into three facies associations (1) clinoforms, (2) tidal to subtidal facies, and (3) lagoonal facies. The clinoforms are sets of very large marine dunes 15–20 m high that prograded N70° across the platform as part of a regressive systems tract. Moldic rhombohedral pore spaces associated with dedolomitization are well-expressed within clinoforms and in the bioturbated levels of lagoonal facies. Drone photogrammetry combined with the "Truncated Gaussian with Trends" algorithm implemented in Petrel® software is used to create a geological model that faithfully reproduces the facies architecture observed in the quarry cliffs. Drone photogrammetry can be combined with field work to describe and locate facies and so constrain the spatial distribution of petrophysical properties. It also helps constraining the shapes of geobodies in the model grid for more realistic geological static models and helps providing 3D petrophysical models from an outcropping analogue for geothermal and petroleum reservoirs. Graphical abstract: Image 1 Highlights: Drone-based photogrammetry in combination with VRGS® and Petrel® softwares. High-resolution Digital Outcrop Modeling of 3D facies and sedimentary structures. Clinoforms from giant, 15–20 m high marine sand waves prograding on the platform. Analogue for carbonate-based geothermal and petroleum reservoirs.